Embedding Building Information Modelling in the Construction Area: A Case within an Undergraduate Civil Engineering Program - Del Savio, Alexandre Almeida; Galantini Velarde, Katerina; Luna Torres, Ana Felicita; Salinas Saavedra, Jose Roberto; Vergara Olivera, Mónica Alejandra (International Journal of Engineering Pedagogy (iJEP), 2024)
Undergraduate programs face the challenge of staying up-to-date by responding to globalization, internationalization, and regionalization processes. Civil engineering programs should meet the requirements of the Architecture, Engineering, Construction, and Operation (AECO) industry. Building Information Modelling (BIM) is a methodology that involves shared digital representations of built assets to facilitate design, construction, and operation processes within the construction knowledge field. The present research describes a methodology with six mechanisms to develop and consolidate BIM-related competencies within the construction area from an undergraduate civil engineering program. It also explores students’ perceptions about the subjects within this area and their relationship with the training and reinforcement of the competencies. The study follows a descriptive scope with an action research design. The principal result is the methodology, which has six mechanisms: (1) BIM implementation into topics and syllabi; (2) use of collaborative platforms; (3) professor training programs; (4) establishment of student organizations; (5) development of a BIM application project; and (6) area and subject meetings. The validation process, which included professors, enrollment, employability and research rates, and the curricular proposal and students’ perceptions, revealed that the mechanisms could effectively support the development and reinforcement of BIM-related competencies.